Essential oil of trees of the genus Ocotea (Lauraceae) in Costa Rica. I. Ocotea brenesii - Chaverri, Carlos; Cicció, José F. (Revista de Biología Tropical, 2005)
The chemical composition of the essential oils from leaves and wood of Ocotea brenesii Standl. growing wild in Costa Rica was determined by capillary GC/FID and GC/MS. From the leaves, 64 compounds were identified, corresponding to 85.9% of the oil, and from the wood 57 compounds were identified corresponding to 69.0% of the oil. The major constituents identified in the leaf oil were α-copaene (21.1%), δ-cadinene (9.2%), spathulenol (7.3%), globulol (5.6%) and β-caryophyllene (5.2%). The major constituents of the wood oil were α-copaene (6.6%), caryophyllene oxide (6.3%), β-caryophyllene (6.1%) and humulene epoxide (4.6%).